Development of Student Worksheet (LKS) Writing Beginnings with Letters Cards and SAS Method to Improve Writing Skills Beginning of Students in Grade 1 Elementary School - Yuhastuti, Nur Kamila; Sudin, Ali; Djuanda, Dadan (Jurnal Pena Ilmiah, 2021)
This research is motivated by the findings of online learning, which are the low initial writing skills and the lack of teaching materials as complementary teaching materials specially to help students write beginning. This study aims to improve the writing skills of first graders at SDN Cikidang II, Majalengka Regency. This research use research and development method. The instruments of data collection use observation guidelines, questionnaires by experts to assess the level of validity of students’ worksheets (LKS) and documentation. The result shows that the validation of the development of student worksheets (LKS) designed by experts carried out in one round with 90% results. Likewise, validation from users which is teacher carried out in one round with 88% results. While the results of material expert validation were carried out in two rounds with the final results of 82%. The results mean that the student worksheet is suitable for use without revision based on the conversation of the assessment criteria.